Accelerating Alzheimer's research through 'natural' animal models. Issue 2 (March 2015) - Braidy, Nady; Poljak, Anne; Jayasena, Tharusha; Mansour, Hussein; Inestrosa, Nibaldo C.; Sachdev, Perminder S.
Abstract : Purpose of review: Alzheimer's disease is a complex multifactorial age-related neurodegenerative disorder. Current transgenic animal models do not fully recapitulate human Alzheimer's disease at the molecular, cellular and behavioural levels. This review aims to address the clinical relevance of using 'physiologically' aged rats, dogs and Octodon degus, as more representative 'natural' ecologically valid models to elucidate mechanistic aspects of Alzheimer's disease, and for the development of therapeutic agents to attenuate age-related cognitive decline. Recent findings: Aged rats, dogs and O. degus decline cognitively and ultimately develop Alzheimer's disease-like symptoms in response to the natural ageing process. Aged rats provide a tractable and popular model to examine the neurobiological basis underlying cognitive decline with age, but they do not develop Alzheimer's disease pathology. Progressive accumulation of abnormal amyloid-beta in extracellular plaques and surrounding cerebral vasculature is a common feature in human Alzheimer's disease, aged canine model and most nonhuman primates. Interestingly, the O. degus develops amyloid-beta deposits, neurofibrillary tangles containing hyperphosphorylated tau protein, altered cholinergic transmission and cognitive deficits analogous to those observed in Alzheimer's disease. Natural animal models better represent the full pathophysiology of Alzheimer's disease and are not only a viable alternative to transgenic models, but also are arguably the preferable model. Summary: 'Natural' models are useful to elucidate the neurobiological basis of Alzheimer's disease and develop effective therapeutic strategies that can be translated into human clinical trials.